Vibrio tapetis Displays an Original Type IV Secretion System in Strains Pathogenic for Bivalve Molluscs - Dias, Graciela M.; Bidault, Adeline; Le Chevalier, Patrick; Choquet, Gwenaëlle; Der Sarkissian, Clio; Orlando, Ludovic; Medigue, Claudine; Barbe, Valerie; Mangenot, Sophie; Thompson, Cristiane C.; Thompson, Fabiano L.; Jacq, Annick; et al. (Frontiers in Microbiology, 2018)
The Brown Ring Disease (BRD) caused high mortality rates since 1986 in the Manila clam Venerupis philippinarum introduced and cultured in Western Europe from the 1970s. The causative agent of BRD is a Gram-Negative bacterium, Vibrio tapetis, which is also pathogenic to fish. Here we report the first assembly of the complete genome of V. tapetis CECT4600T, together with the genome sequences of sixteen additional strains isolated across a broad host and geographic range. Our extensive genome dataset allowed us to describe the pathogen pan- and core genomes and to identify putative virulence factors. The V. tapetis core genome consists of 3,352 genes, including multiple potential virulence factors represented by haemolysins, transcriptional regulators, Type I restriction modification system, GGDEF domain proteins, several conjugative plasmids, and a Type IV secretion system. Future research on the coevolutionary arm race between V. tapetis virulence factors and host resistance mechanisms will improve our understanding of how pathogenicity develops in this emerging pathogen.